Digital Transformation on Manufacturing, Infrastructure & Service DTMIS 2022 - Ilin, Igor; Petrova, Mariana Mateeva; Kudryavtseva, Tatiana (Lecture Notes in Networks and Systems, 2023)
XIV, 1023 p. 256 illus., 177 illus. in color.